Socio-Emotional and Cognitive Development in Intrauterine Growth Restricted (IUGR) and Typical Development Infants: Early Interactive Patterns and Underlying Neural Correlates. Rationale and Methods of the Study - Sacchi, Chiara; De Carli, Pietro; Mento, Giovanni; Farroni, Teresa; Visentin, Silvia; Simonelli, Alessandra (Frontiers in Behavioral Neuroscience, 2018)
Intrauterine growth restriction (IUGR) is defined as a fetal growth retardation, resulting in an estimated fetal weight less than the 10th centile for gestational age. Developing brain of IUGR infants is affected by the atypical fetal growth, presenting altered structure and connectivity and increased risk for neurodevelopmental impairments. Behaviorally, IUGR infants show reduced responsiveness and engagement with human faces during mother-child exchanges. The neural mechanisms of these patterns of interactions remain unexplored. Aim of this research project will be to longitudinally investigate the cognitive and behavioral outcomes of IUGR infants at 12 months. Mother-infant interactions and ERP components of face processing (infant N170, P400, Nc) in 4 and 9 months IUGR will be studied as potential early markers of the hypothesized atypical development. Thirty IUGR participants will be recruited after receiving the in-utero diagnosis (>28th gestational week). Thirty healthy infants will be enrolled as the control group. Maternal environment will be assessed via Emotional Availability Scales, with child responsiveness and maternal sensitivity as variables of interest. Infants’ scalp-recorded cortical activity in response to social and non-social stimuli will be investigated using a high-density EEG system (EGI Geodesic system). Neurodevelopment will be measured at 12 months of child’s life, using Bayley Scales for Infant Development, while the possible presence of emotional-behavioral problems will be rated via Child Behavior Checklist. We expect that being IUGR significantly affects cognitive and behavioral outcomes at 12 months, through mediation effects of both infants’ neural and behavioral capacity to respond to social stimuli. Indeed, we expect an altered response to social stimuli in IUGR infants, resulting in smaller ERP components amplitude in response to human faces compared to healthy matched peers. A significant association between neural response to social stimuli and infants’ responsiveness to maternal stimulation during interactions is expected, with impoverished performances on the interactive domain in IUGR, compared to healthy peers. This study will enhance understanding on neural mechanisms underpinning the interactive patterns sustaining socio-cognitive development in IUGR and healthy infants. The study will help in clarifying the role of postnatal environment in buffering the vulnerability experienced by children delayed in their fetal growth.